The Global Smartphone Beyond a youth technology - Miller, Daniel (Ageing with Smartphones, 2021)
The smartphone is often literally right in front of our nose, so you would think we would know what it is. But do we? To find out, 11 anthropologists each spent 16 months living in communities in Africa, Asia, Europe and South America, focusing on the take up of smartphones by older people. Their research reveals that smartphones are technology for everyone, not just for the young. The Global Smartphone presents a series of original perspectives deriving from this global and comparative research project. Smartphones have become as much a place within which we live as a device we use to provide 'perpetual opportunism', as they are always with us. The authors show how the smartphone is more than an 'app device' and explore differences between what people say about smartphones and how they use them. The smartphone is unprecedented in the degree to which we can transform it. As a result, it quickly assimilates personal values. In order to comprehend it, we must take into consideration a range of national and cultural nuances, such as visual communication in China and Japan, mobile money in Cameroon and Uganda, and access to health information in Chile and Ireland - all alongside diverse trajectories of ageing in Al Quds, Brazil and Italy. Only then can we know what a smartphone is and understand its consequences for people's lives around the world.